Energy Justice Across Borders 2019
DOI: 10.1007/978-3-030-24021-9_1
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Ethics Justice Across Borders: The Role of Global Philosophy

Abstract: Our energy systems are truly international, and yet even now, our energy policies tend to be grounded at the national level and in many instances, remain illequipped to tackle transboundary energy issues. Our energy policy systems are also largely detached from the concerns of ethics or justice. It follows that we must find new and innovative ways of not conceptualising these normative issues, but of operationalising response to them. This book stems from the emergent gap: the need for comparative approaches t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Apart from limited interaction with practice, we also observe that the Energy Justice literature has largely developed without interdisciplinary insights from established philosophical approaches to justice in the energy domain. Indeed, at present, the predominant underpinning of Energy Justice research is Western philosophy and humancentred approaches only [4,139,149] and in many cases, most Energy Justice studies have focused only on a descriptive account of the triumvirate of tenets. Sovacool et al [4] have explored several alternative non-western philosophies and their potential to strengthen Energy Justice theory, yet this field is embryonic.…”
Section: Limited Philosophical Exposurementioning
confidence: 99%
“…Apart from limited interaction with practice, we also observe that the Energy Justice literature has largely developed without interdisciplinary insights from established philosophical approaches to justice in the energy domain. Indeed, at present, the predominant underpinning of Energy Justice research is Western philosophy and humancentred approaches only [4,139,149] and in many cases, most Energy Justice studies have focused only on a descriptive account of the triumvirate of tenets. Sovacool et al [4] have explored several alternative non-western philosophies and their potential to strengthen Energy Justice theory, yet this field is embryonic.…”
Section: Limited Philosophical Exposurementioning
confidence: 99%
“…Over the last decade, energy has increasingly been developing into an object of interest of scholars operating in the social sciences. Inspired by a longer tradition of studies in environmental humanities, and environmental justice in particular (Bullard, 1996(Bullard, , 2000Martinez-Alier, 2003;Walker, 2012;Agyeman et al, 2003), students in the energy humanities have started reflecting on possible applications and adaptations of theoretical and empirical tools developed in that older tradition, to their own domain of expertise (McCauley et al, 2013;Sovacool and Dworkin, 2014;Sovacool et al, 2017;Monyei et al, 2018;Bombaerts et al, 2020;Pellegrini-Masini et al, 2020). These publications have rapidly multiplied (Simcock and Mullen, 2016;Jenkins et al, 2017;McCauley et al, 2019;Bombaerts et al, 2020).…”
Section: Energy Justice In Under-the-grid Settlementsmentioning
confidence: 99%
“…Inspired by a longer tradition of studies in environmental humanities, and environmental justice in particular (Bullard, 1996(Bullard, , 2000Martinez-Alier, 2003;Walker, 2012;Agyeman et al, 2003), students in the energy humanities have started reflecting on possible applications and adaptations of theoretical and empirical tools developed in that older tradition, to their own domain of expertise (McCauley et al, 2013;Sovacool and Dworkin, 2014;Sovacool et al, 2017;Monyei et al, 2018;Bombaerts et al, 2020;Pellegrini-Masini et al, 2020). These publications have rapidly multiplied (Simcock and Mullen, 2016;Jenkins et al, 2017;McCauley et al, 2019;Bombaerts et al, 2020). Unsurprisingly (more on this point in Section 3), most of them have initially focussed on the Global North, and there is still today a strong bias towards that region [Sovacool et al, 2020, p. 21].…”
Section: Energy Justice In Under-the-grid Settlementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical studies have shown that citizens evaluate the local placing of a technology differently than the placing of the technology elsewhere (Midden and Huijts 2009;Terwel and Daamen 2012;Bombaerts et al 2020), for instance because of the attachment that people have to the place they live (Devine-Wright and Howes 2010). Moreover, knowing about the local context in which a technology is implemented, people are able to reflect on its concrete and immediate repercussions.…”
Section: The Institutional Reproduction Of Dominant Perspectivesmentioning
confidence: 99%